Evaluation of a hospital-based integrated model of eye care for diabetic retinopathy assessment: a multimethod study. Issue 4 (30th April 2020) - Long, Janet C; Blakely, Brette; Mahmoud, Zeyad; Ly, Angelica; Zangerl, Barbara; Kalloniatis, Michael; Assaad, Nagi; Yapp, Michael; Clay-Williams, Robyn; Braithwaite, Jeffrey
Abstract : Objectives: Diabetic eye disease is a leading cause of blindness but can be mitigated by regular eye assessment. A framework of issues, developed from the literature of barriers to eye assessment, was used to structure an examination of perceptions of a new model of care for diabetic retinopathy from the perspective of staff using the model, and health professionals referring patients to the new service. Design: Multimethod: interviews and focus groups, and a separate survey. Setting: A new clinic based on an integrated model of care was established at a hospital in outer metropolitan Sydney, Australia in 2017. Funded jointly by Centre for Eye Health (CFEH) and the hospital, the clinic was equipped and staffed by optometrists who work alongside the ophthalmologists in the existing hospital eye clinic. Participants: Five (of seven) hospital staff working in the clinic (ophthalmologists and administrative officers) or referring to it from other departments (endocrinologists); nine optometrists from CFEH who developed or worked in the clinic; 10 community-based optometrists as potential referrers. Results: The new clinic was considered to have addressed known barriers to eye assessment, including access, assistance for patients unable/unwilling to organise eye checks and efficient management of human resources. The clinic optimised known drivers of this model of care: providing clear scope of practice and protocols for shared care between optometrists and ophthalmologists, good communication between referrers and eye professionals and a collegial approach promoting interprofessional trust. Remaining areas of concern were few referrals from general practitioners, fewer referrals from hospital endocrinologists than expected and issues with stretched administrative capacity. There were also perceived mismatches between the priorities of hospital management and aims of the clinic. Conclusions: The new model was considered to have addressed many of the barriers to assessment. While there remain issues with the model, there were also unexpected benefits.